Autonomous Control Architecture of Satellite Intelligent Computing Platform - GAO Jixing; XU Zhiping; DING Wenhui; DING Xihao; LIU Zhixin; YU Zhigang; LU Zhou (天地一体化信息网络)
In order to meet the service quality requirements of emerging applications such as mobile Internet of things and intelligent logistics, with the progress of space and information technology, it has become one of the main methods to shorten the response time by deploying intelligent computing platforms in satellites for on-orbit data processing. At present, the scale of low-orbit satellites is huge, and they are often in areas that are difficult to directly measure and control, and there have many working modes, so they need the ability of independent control. Based on the introduction of the research status of the satellite intelligent computing platform, this paper analyzed the functional requirements of the satellite intelligent computing platform. On the basis of designing a set of general and open hardware architecture of satellite intelligent computing platform, this paper put forward the idea of autonomous management and control software architecture of satellite intelligent computing platform, and further described the internal composition and working principle of main control components, management and control components and collaborative components. On this basis, the key technologies related to autonomous management and control software were analyzed. Finally, the development direction of autonomous control software of satellite intelligent computing platform was prospected.